A constituição do ethos discursivo no periódico “Legionário” - Zaghi, Luis Henrique Lodi (2018)
Based on studies of French Speech Discourse Analysis the present research, whose theme is the constitution of the discursive ethos in the unofficial organ of the Archdiocese of São Paulo, The Legionary, published in the first half of the twentieth century, aims to present an understanding of how it happened the constitution of the discursive ethos in this periodical. The corpus chosen as empirical material for analysis were 11 articles by the main editor, director and inspirer of the Legionnaire, Plinio Corrêa de Oliveira. The discourse authored by this enunciator, analyzed in the cutouts highlighted for this analysis, has a strong relationship of interdiscursivity with the publications emanating from documents of the popes of the time, besides being deeply related to the doctrinal sources of ultramontane Catholicism of the time. We analyze how the interdiscursivity character represented in the interrelation of voices manifested in multiple tones, emanating from the enunciator and the “other” present in the discourse produced the discourse ethos understood under the approach of AD theorist Dominique Maingueneau. We consider that the ethos has deep relation with the construction of identity that is constituted by this interdiscursivity concretized in the discursive materiality. We understand that the present study can contribute to an understanding of the constitution of the ethos that proceeds from journalistic discourse and, in the specific case of this research, with clear marks of moral and religious authority